EDITORIAL - de Freitas de Mello Junior, Alexandre; Ferreira Marques Neto, Antonio; Rocha Machado, Bianca; Castelo Branco Medeiros, Felipe; Tavares Borges, Gabriela; Mendes Junior, Gilmar Jorge; Noleto Ferreira, Lennon Pedro; Möller, Mathias Alberto; Santos Lapa, Raphael; Martins Mendes, Ruth de Paula; Rossineti Rufinoni, Priscila (PÓLEMOS – Revista de Estudantes de Filosofia da Universidade de Brasília, 2013)
Editorial do volume 02, número 03, ano 2013.